PENINGKATAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK MELALUI PENERAPAN PROBLEM BASED LEARNING TERINTEGRASI PENDIDIKAN LINGKUNGAN - Tasya Setya Nia Wati; Nurita Apridiana Lestari (STKIP Subang, 2026)
Critical thinking skills are one of the essential competencies that students need to develop in order to face the challenges of 21st-century learning. However, students' critical thinking skills remain relatively low due to teacher-centered learning practices and limited connections between learning materials and real-world environmental issues. This study aimed to analyze the improvement of students' critical thinking skills through the implementation of an environmental education-integrated Problem Based Learning (PBL) model on the topic of temperature and heat. This research employed a quasi-experimental method using a Nonequivalent Control Group Design. The participants consisted of students from class XI-1 as the experimental group and class XI-2 as the control group at SMAN 22 Surabaya. The research instrument was an essay-based critical thinking test developed according to Facione's critical thinking indicators, including interpretation, explanation, inference, analysis, and evaluation. The data were analyzed using normalized gain (N-Gain) scores to determine the improvement in students' critical thinking skills. The results showed that the experimental class achieved an N-Gain score of 0.702, categorized as moderate, while the control class obtained an N-Gain score of 0.269, categorized as low. Indicator-based analysis revealed that the evaluation indicator showed the highest improvement with an N-Gain score of 0.755, while the interpretation indicator showed the lowest improvement with an N-Gain score of 0.654. These findings indicate that the implementation of an environmental education-integrated PBL model is effective in improving students' critical thinking skills on the topic of temperature and heat.